UTILIZATION OF CARBOHYDRATE POTENTIAL IN VARIOUS KINDS OF BANANA COB FLOUR BANANA IN KACANG GOATS - A., Aswandi; Syaefullah, B. L.; Iyai, D.A.; Wajo, M. Jen. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The objective of this research was to observe the productivity in kacang goats which were given a complete feed containing flour of various types of banana plant weevils. The material studied in this study was six complete types of feed. Complete feed containing weevil flour from 5 banana plant varieties. Complete feed is prepared with a complete feed composition. The cattle used were 18 male bean goats, mean initial body weight, 15.42 ± 1.98 kg (CV: 13.73%) aged 10-15 months. Livestock is given complete feed containing banana weevil flour for 60 days. The cage is 12 m x 6m in size, construction has a floor platform as high as 140 cm, the enclosure is 1 x 1 m in size and 130 cm in height, equipped with a drinking area. The treatment was in the form of 6 complete types of feed with different formulations, consisting of CF0, CF1, CF2, CF3, CF4, and CF5 containing banana weevil flour with different varieties and control treatment (CF0). The research design used was a completely randomized design with five treatments of complete feed formulas containing hump flour of various banana varieties.The results of the research that the complete feed formulation containing Batu banana hump flour (CF2) and Kapok (CF3) produced the best productivity and performance response of Kacang goat. compared to treatment; CF0 CF1; CF4 and CF5.